Hipolito Unanue in Cadiz - Alvarez-Carrasco, Ricardo I. (2020)
Hipólito Unanue's participation in the Cortes of Cádiz has not been the subject of a detailed investigation that allows to know his public and private performance during his stay in Spain. The purpose of this article is to make a first approach to this under-studied episode of the life of the "father of Peruvian medicine".